2017
DOI: 10.1371/journal.pone.0190139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of residential displacement on healthcare access and mental health among original residents of gentrifying neighborhoods in New York City

Abstract: ObjectivesAs gentrification continues in New York City as well as other urban areas, residents of lower socioeconomic status maybe at higher risk for residential displacement. Yet, there have been few quantitative assessments of the health impacts of displacement. The objective of this paper is to assess the association between displacement and healthcare access and mental health among the original residents of gentrifying neighborhoods in New York City.MethodsWe used 2 data sources: 1) 2005–2014 American Comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 21 publications
2
70
0
Order By: Relevance
“…Researchers have commonly used a threshold strategy in which neighborhood changes in housing prices and household incomes, for example, are compared to set thresholds . Other quantitative strategies involve ranking neighborhood change indicators and the use of principal component analysis (PCA) . We recognize that different strategies for developing a gentrification variable, when used as an independent variable, can produce conflicting results .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have commonly used a threshold strategy in which neighborhood changes in housing prices and household incomes, for example, are compared to set thresholds . Other quantitative strategies involve ranking neighborhood change indicators and the use of principal component analysis (PCA) . We recognize that different strategies for developing a gentrification variable, when used as an independent variable, can produce conflicting results .…”
Section: Methodsmentioning
confidence: 99%
“…Higher‐income older adults in gentrifying neighborhoods also reported poorer mental health than their counterparts in low‐income neighborhoods . In cohort studies, low‐income children who lived in gentrified New York City neighborhoods had higher prevalence of anxiety or depression compared to children who lived in other neighborhoods, and displaced residents of gentrifying neighborhoods had greater risks for emergency department visits, hospitalizations, and mental health‐related visits than residents who remained …”
Section: Introductionmentioning
confidence: 99%
“…Multiple health outcomes were not associated with gentrification [19, 21, 23-25, 30, 36, 37, 48, 49]. Health outcomes that were associated with gentrification included: self-reported health [18,21,22,25,32,44], preterm birth [23], mental health conditions [19,32,38,44], alcohol and drug use [24,27,43,47], psychosocial factors [17,20,28,31,33,40,42,46,49], and health care utilization [26].…”
Section: Overviewmentioning
confidence: 99%
“…Rent payment or concerns about rent payment are often associated with mental fatigue. A recent study found that involuntary residential moves due to gentrification are highly associated with mental health deterioration, emergency room visits, and hospitalization [ 15 ]. Frequent residential mobility due to renters’ involuntary moves or residential instability may cause health-related problems during the process of seeking residential stability.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that the association between housing instability and health status or health behavior is closely related to loss of housing, overcrowding experienced by those who have to live in shared housing to save money, and residential mobility. Some studies, for instance, suggest that housing loss causes mental illness because it decreases one’s feeling of personal control and induces stress [ 15 , 16 , 17 ]. Negative health behaviors likely associated with stress from housing instability include drug abuse and unhealthy eating habits, which can lead to chronic diseases [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%